1996
DOI: 10.1046/j.1365-2249.1996.d01-642.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human colonic dendritic cells and macrophages

Abstract: SUMMARYTo define the phenotype of intestinal dendritic cells and macrophages, resected colonic specimens were used to obtain lamina propria cell suspensions by EDTA treatment, then enzymatic digestion. The phenotype of dendritic cell-enriched suspensions was compared with that of macrophage-enriched populations by immunocytochemistry using the avidin-biotin-peroxidase (ABC) system and immunoelectron microscopy. Dendritic cells expressed HLA-DR (L243) and HLA-DQ-associated (RFD1) antigens and CD68 in a perinucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 24 publications
4
36
0
1
Order By: Relevance
“…Different DC subsets have been described in the intestine, including the lamina propria and Peyer's patches (16,26,27). In general, the expression of MHC-II and the characteristic irregular morphology have been used to identify these cells in situ (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…Different DC subsets have been described in the intestine, including the lamina propria and Peyer's patches (16,26,27). In general, the expression of MHC-II and the characteristic irregular morphology have been used to identify these cells in situ (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal monocytes, which constitute 10 20% of mononuclear cells in the lamina propria, differ markedly in phenotype and function from peripheral blood monocytes (16,40). The classical monocyte-specific surface antigens CD14 (LPS co-receptor), CD11b (complement receptor 3, CR3) and CD16 (FcγIII receptor) are expressed at low levels in the normal intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about DC in the human intestine. Cell populations with phenotypic properties consistent with DC have been identified in a number of immunocytochemical studies (12)(13)(14), and partially enriched populations of these cells have been shown to stimulate primary T cell responses in a primary allogeneic MLR (15). Detailed analysis of the phenotype and function of these cells is currently lacking.…”
Section: /Ox41mentioning
confidence: 99%